Antitumor effects of oncolytic herpes simplex virus type 2 against colorectal cancer in vitro and in vivo - Yin L; Zhao C; Han J; Li Z; Zhen Y; Xiao R; Xu Z; Sun Y (Dove Medical Press, 2017)
Lei Yin,1–3 Chunhong Zhao,3 Jixia Han,4 Zengjun Li,2 Yanan Zhen,3 Ruixue Xiao,3 Zhongfa Xu,3 Yanlai Sun2 1School of Medicine and Life Sciences, University of Jinan-Shandong Academy of Medical Sciences, Jinan, 2Department of Gastrointestinal Cancer Surgery, Shandong Cancer Hospital Affiliated to Shandong University, Shandong Academy of Medical Sciences, Jinan, 3Department of Gastrointestinal Surgery, The Affiliated Hospital of Shandong Academy of Medical Sciences, Jinan, 4Department of General Surgery, The Sixth People’s Hospital of Jinan, Jinan, People’s Republic of China Background: The incidence of colorectal cancer (CRC) is on the rise. Furthermore, late-stage diagnoses and limited efficacious treatment options make CRC a complex clinical challenge. Therefore, a new therapeutic regimen with a completely novel therapeutic mechanism is necessary for CRC. In the present study, the therapeutic efficacy of oncolytic herpes simplex virus type 2 (oHSV2) in CRC was assessed in vitro and in vivo. oHSV2 is an oncolytic agent derived from herpes simplex virus type 2 that encodes granulocyte-macrophage colony-stimulating factor.Materials and methods: We investigated the cytopathic effects of oHSV2 in CRC cell lines using the MTT assay. Then, cell cycle progression and apoptosis of oHSV2 were examined by flow cytometry. We generated a model of CRC with mouse CRC cell CT26 in BALB/c mice. The antitumor effects and adaptive immune response of oHSV2 were assessed in tumor-bearing mice. The therapeutic efficacy of oHSV2 was compared with the traditional chemotherapeutic agent, 5-fluorouracil.Results: The in vitro data showed that oHSV2 infected the CRC cell lines successfully and that the tumor cells formed a significant number of syncytiae postinfection. The oHSV2 killed cancer cells independent of the cell cycle and mainly caused tumor cells necrosis. The in vivo results showed that oHSV2 significantly inhibited tumor growth and prolonged survival of tumor-bearing mice without weight loss. With virus replication, oHSV2 not only resulted in a reduction of myeloid-derived suppressor cells and regulatory T cells in the spleen, but also increased the number of mature dendritic cells in tumor-draining lymph nodes and the effective CD4+T and CD8+T-cells in the tumor microenvironment.Conclusion: Our study provides the first evidence that oHSV2 induces cell death in CRC in vitro and in vivo. These findings indicate that oHSV2 is an effective therapeutic cancer candidate that causes an oncolytic effect and recruits adaptive immune responses for an enhanced therapeutic impact, thus providing a potential therapeutic tool for treatment of CRC. Keywords: colorectal cancer, oncolytic virus, herpes simplex virus type 2, granulocyte–macrophage colony-stimulating factor, immunotherapy, gene therapy